The Wednesday wars - Schmidt, Gary D. (Boston : Houghton Mifflin Harcourt, 2007)
Seventh-grader Holling Hoodhood, stuck in Mrs. Baker's classroom during the 1967 school year while his classmates go to either Catechism or Hebrew school, learns much of value about the world in which he lives from the study of the plays of William Shakespeare.
"Sandpiper."
Newbery Medal/Honor
Wilson's Children
Wilson's Junior High School
Book Links-starred, September 2007
Booklist starred, June 2007
Keywords: Shakespeare, William, -- 1564-1616. -- Juvenile fiction; Shakespeare, William, -- 1564-1616. -- Fiction; Shakespeare, William, -- 1564-1616. -- Fiction; Families -- New York (State) -- Long Island -- Juvenile fiction; Junior high schools -- Juvenile fiction; Schools -- Juvenile fiction; Coming of age -- Fiction; Family life -- New York (State) -- Long Island -- Fiction; Junior high schools -- Fiction; Schools -- Fiction; Bildungsromans; Family life -- Long Island (N.Y.) -- Fiction; Junior high schools -- Fiction; School stories; Long Island (N.Y.) -- History -- 20th century -- Juvenile fiction; Long Island (N.Y.) -- History -- 20th century -- Fiction; Long Island (N.Y.) -- History -- Fiction; Bildungsromans